FORENSIK JARINGAN UNTUK INVESTIGASI KEJAHATAN CYBER PADA STUDI KASUS PEMBOBOLAN DATA KOMINFO OLEH BJORKA - Aspiani Putri Ashilah; Rakhmadi Rahman (Jurnal Riset Sistem Informasi, 2024)
The study is to investigate the phenomenon of cybercrime, specifically focusing on the Bjorka data breach at Kominfo. Cybercrime has grown to be a serious threat to Indonesia's cyber security, including data theft, hacking, and malware attacks. This study approach employs qualitative descriptive techniques via a methodical examination of documents, including journal articles from both domestic and foreign publications. Based on analysis, it was found that Bjorka committed data breaches to protest government policies and highlight security weaknesses. The study also explores measures to prevent cybercrime, such as the use of security technology, user training, and the implementation of strict security policies. Encryption tools like Veracrypt should be used to protect sensitive data from theft. The research results are expected to raise awareness and collaborative efforts among governments, associated organizations, and communities to address the threat of cybercrime as well as strengthen national cyber defences